DIGITAL ETHICS AND CITIZENSHIP CHALLENGES IN CYBERSPACE: AN OVERVIEW FROM PERSPECTIVE MORALS AND LAWS - Happy Budyana Sari; Ni Made Ayu Priska Cahya Ningsih; Ni Made Yuli Kristina; Ni Putu Indah Rismayanti; Emmy Febriani Thalib; Ni Putu Suci Meinarni; Lis Julianti (Warmadewa Press, 2024)
Digital ethics involve moral principles and values that govern behavior individuals and groups in digital environments. Digital ethics involves deep responsibility disseminate accurate information, maintain the quality of online communication and interaction, and awareness of the social and environmental impact of the use of digital technology. This study uses a literature study method with a descriptive qualitative approach to study ethics and challenges of citizenship in cyberspace from a moral and legal perspective. Through data analysis, found several important digital ethical concepts in dealing with challenges in cyberspace, such as responsibility in disseminating information, privacy protection and data security, digital awareness, respect for freedom of expression, verification information, and respect intellectual property rights. From a moral and legal perspective, comprehensive regulation is needed to regulate the use of digital technology, enforcement effective law against digital ethics violations, legal education and awareness, and development of online communication ethics. Challenges of citizenship faced in the world cyber through a moral and legal perspective including the spread of harmful content, respect to privacy and data, cyberbullying behavior, and use of inappropriate language. Legal regulation, protection against cyber crime, and a balance between freedoms speaking and legal boundaries are also challenges that need to be overcome.